Investigation into the effectiveness of cutting parameters on wear regions of the flank wear curve and associated cutting tool life improvement - Altan, Erhan; Uysal, Alper; Caliskan, Oguz (INDERSCIENCE ENTERPRISES LTD, 2018)
In machining operations, less tool wear and superior tool life are desired. Therefore, the effects of cutting parameters on tool life should be known and optimal cutting parameters should be chosen to reduce tool wear. In this study, the effectiveness values of cutting parameters on each wear region in the cutting tool flank wear curve were investigated to improve cutting tool service life. For this reason, some statistical methods were employed to determine them and the results were verified by experimental studies. In the initial tool wear and the rapid tool wear regions, the most effective parameter was found as the feed and the tool wear increased with increase of the feed. In the steady-state tool wear region, the effectiveness values of the cutting speed and the feed were very close to each other, but the cutting speed was determined a little more effective.
Keywords: tool life; flank wear; wear regions; turning; Taguchi method; CARBIDE; MECHANISMS; STEEL; Materials Science